Diseño y construcción de un equipo para evaluar el calor específico de líquidos y la conductividad térmica de materiales sólidos - Arista Sifuentes, Jorge Luis (2024)
The general objective of this thesis was to design and build a device to evaluate the specific heat of liquids and the thermal conductivity of solid materials. The device is composed of the following components: a stainless steel parallelepiped box, an electric heater as the heat source, and the following digital instruments: a temperature controller with a thermocouple sensor, an infrared digital thermometer, a metal probe thermometer, and a voltage and amperage meter. The liquids used had a mass of 0.2 kg and included: aguaje juice (with 12 % dissolved solids) and sugar solutions at: 10 %, 25 % and 40 % by weight. The specific heat values obtained were: 3889.80 J/(kg.°C), 3928.24 J/(kg. °C), 3592.21 J/(kg.°C) y 3530.92 J/(kg.°C), respectively. This indicated that the higher the concentration of dissolved solids, the lower the corresponding specific heat, demonstrating an inverse relationship between these two variables. The solids tested were: screw pine wood, marupa wood, wheat flour, brown sugar, and white sand, resulting in thermal conductivity values of: 00.19 W/(m.°C), 0.14 W/(m.°C), 0.12 W/(m.°C), 0.15 W/(m.°C) y 0.16 W/(m.°C), respectively. This indicated that wheat flour and screw pine wood are the solids with the lowest and highest heat conduction capabilities, respectively. Thus, this thesis has been completed, achieving the general objective and testing the general hypothesis.